(untitled) (diségno, 2025)
In the following note –without delving into the broader topic of drawing as language, or seeking to establish the connections between verbal and graphic forms of communication– I take the opportunity to organize some reflections that have emerged over recent decades. These reflections have shown a certain practical effectiveness in educational and didactic contexts, and are based on references that are not particularly recent, yet far from obsolete. [read more]